Mejora del sistema de presupuestos y control de costos de la empresa ESMERA S.A. - Guzmán-Alfaro, Walter Delfín (Instituto Tecnológico de Costa Rica, 2016)
In this report is presented a proposal to improve the budget system and cost control of the company ESMERA SA, as a result of graduation project in the modality of directed professional practice. This improvement proposal is raised as a response to the needs that this company has especially in the budget area and the budget control in the execution of works. For the development of this project, the general objective raised is to propose an improvement of the budget system and cost control with emphasis in the area of manpower of the company. Among the results obtained, they stand a database with manpower yields, measured in the workshop, the diagnosis, and the redesign of the system of budget estimation, including the calculation of manpower by yields, and finally a system to control the costs in the implementation of projects. At the end of the project, it is possible to conclude that through the development of the objectives raised. It was possible to streamline the procedure for calculating and reliability of results.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Rendimiento laboral; Construcción; Mano de Obra; Estructura; Estructuras de Acero